Pengaruh Terpaan Media Tentang Covid-19 Terhadap Kecemasan Masyarakat Pada Pemberitaan Bontangpost.id Di Bontang Permai Kelurahan Api-Api - Andi Ainun Namri (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
This study aims to determine whether there is an influence of media exposure about covid-19 on public anxiety on bontangpost.id reporting in Bontang Permai, Api-Api village. Variable X in this study is bontangpost.id media exposure about covid-19, while variable Y in this study is public anxiety. The method and type of research used by the researcher is a quantitative explanatory research with a sampling technique that is purposive sampling. The theory used is the theory of media dependence (Dependency Theory) where the more a person depends on a media to meet their needs, the more important the media becomes for that person. Based on the data obtained by simple linear regression analysis, the results obtained are Y = 7,407 + 0,468X and obtained a t count value of 9,078 > t table 1,998, this number indicates that the number of t counts is more than the number of t tables so that it can be stated that there is an influence of media exposure on the news of covid-19 on bontangpost.id on the level of anxiety of the residents of Bontang Permai, Api-Api Village. With a significance value of 0.000 0.05, then Ho is rejected, Ha is accepted. This shows that partially Ha, which states that the news of covid-19 (X) has a significant positive effect on the level of anxiety (Y) of the residents of Bontang Permai, Api-Api Village.